Being Agile in a Novel World - Steve Williams (Gregynog Colloquium 2020, 2020)
Gilbert Ryle suggested to us in 1979 that in 'a partly novel situation, the response is necessarily partly novel, else it is not a response.' Academic libraries across Wales have both aimed to respond, but also to address the novel characteristics presented by a pandemic in the 21st Century: even 10 years ago the technological limitations would have been much more significant to the shift to online learning; the opportunity to work flexibly is something that many would like to continue post-pandemic; staff and student engagement online is many cases is higher than in-person, staff and student wellbeing has become a significant priority; and so forth. How do we learn from this experience and how do we best create a new future for ourselves and our services?